The Effect of Aerobic Training with Vitamin D on Extrinsic Pathway of Apoptosis and Anti- Apoptotic Indices of Heart Tissue of Rats Exposed to Oxidative Damage Induced by H2O2 - Mehdi Pirooz; Mohammad Ali Azarbayjani; Maghsood Peeri; Seyed Ali Hosseini (Islamic Azad University, 2017)
Introduction: Apoptosis plays an important role in the development of cardiovascular diseases. The aim of this study was to investigate the effect of aerobic training (AT) with Vitamin D (VD) on extrinsic pathway of apoptosis and anti- apoptotic indices of heart tissue of rats exposed to oxidative damage induced by H2O2. Methods: In this experimental study, 60 rats were selected and randomly placed into 10 groups of six, including 1) 1 mmol / kg H2O2, 2) 2 mmol / kg H2O2, 3) VD + 1 mmol / kg H2O2, 4) AT + 1 mmol / kg H2O2, 5) AT + VD + 1 mmol / kg H2O2, 6) VD + 2 mmol / kg H2O2, 7) AT + 2 mmol / kg H2O2, 8) AT + VD + 2 mmol / kg H2O2, 9) sham and 10) control. During eight weeks, the rats in groups 1-9 were subjected to intraperitoneal injection of H2O2 at specific doses three times a week; the rats in groups 4, 5, 7 and 8 performed aerobic trainings, and the rats in groups 3, 5, 6 and 8 received 0.5 μg / kg of vitamin D3 intraperitoneally daily. Protein concentrations of Caspase 8, Fas and FLIP were measured in rat heart tissue. For analysis of the research findings, Kolmogorov- Smirnov, one-way ANOVA, two-way ANOVA along with Bonferroni post hoc tests were used (p≤0.05). Results: H2O2 has a significant effect on the increase of Caspase 8, Fas and FLIP in the heart tissue of rats (p≤0.05); eight weeks of aerobic training and Vitamin D intake has a significant effect on decreasing the concentration of Caspase 8, Fas and increase of FLIP in the heart tissue of rats exposed to oxidative damage induced by 1 and 2 m/mol/kg H2O2 (p ≤0.05); aerobic training and Vitamin D intake has significant interactions in the reduction of Caspase 8, Fas in the heart tissue of rats exposed to oxidative damage induced by 1 and 2 m/mol/kg H2O2 (p≤0.05), however, it does not have interactive effect on the increased FLIP of the heart tissue of rats exposed to oxidative damage induced by 1 and 2 m/mol/kg H2O2 (p≥0.05). Conclusion: It seems that performing aerobic training activities and simultaneous consumption of vitamin D supplement has interactive effects on reducing some of the extrinsic pathway indices of apoptosis in the heart tissue of H2O2-rats exposed to oxidative damage induced by H2O2.